Alternative oxidase‐mediated respiration prevents lethal mitochondrial cardiomyopathy. Issue 1 (10th December 2018) - Rajendran, Jayasimman; Purhonen, Janne; Tegelberg, Saara; Smolander, Olli‐Pekka; Mörgelin, Matthias; Rozman, Jan; Gailus‐Durner, Valerie; Fuchs, Helmut; Hrabe de Angelis, Martin; Auvinen, Petri; Mervaala, Eero; Jacobs, Howard T; et al.
Abstract: Alternative oxidase (AOX) is a non‐mammalian enzyme that can bypass blockade of the complex III‐IV segment of the respiratory chain (RC). We crossed a Ciona intestinalis AOX transgene into RC complex III (cIII)‐deficient Bcs1l p.S78G knock‐in mice, displaying multiple visceral manifestations and premature death. The homozygotes expressing AOX were viable, and their median survival was extended from 210 to 590 days due to permanent prevention of lethal cardiomyopathy. AOX also prevented renal tubular atrophy and cerebral astrogliosis, but not liver disease, growth restriction, or lipodystrophy, suggesting distinct tissue‐specific pathogenetic mechanisms. Assessment of reactive oxygen species (ROS) production and damage suggested that ROS were not instrumental in the rescue. Cardiac mitochondrial ultrastructure, mitochondrial respiration, and pathological transcriptome and metabolome alterations were essentially normalized by AOX, showing that the restored electron flow upstream of cIII was sufficient to prevent cardiac energetic crisis and detrimental decompensation. These findings demonstrate the value of AOX, both as a mechanistic tool and a potential therapeutic strategy, for cIII deficiencies. Synopsis: Bcs1l mutant mice show respiratory chain cIII dysfunction resulting in poor electron and proton transfer, and quinol oxidation. This study makes use of alternative oxidase (AOX), an enzyme that shunts electrons from quinols directly to oxygen, thus restoring electron flow upstream of cIII. Broadly expressed transgenic AOX prevents lethal cardiomyopathy in Bcs1lp.S78G knock‐in mice and extends their median survival from 210 to 590 days. Restoration of electron flow upstream of cIII by AOX is sufficient to prevent the cardiac decompensation. AOX prevents pathological changes in the expression of central transcriptional regulators of substrate utilization and metabolic stress in the heart. Analyses of reactive oxygen species (ROS) production and damage suggest that ROS are not instrumental in the rescue. Abstract : Bcs1l mutant mice show respiratory chain cIII dysfunction resulting in poor electron and proton transfer, and quinol oxidation. This study makes use of alternative oxidase (AOX), an enzyme that shunts electrons from quinols directly to oxygen, thus restoring electron flow upstream of cIII.